The Impact of Affiliate Credibility on Perceived Risk and Transaction Value Digital Consumer (Pusat Riset dan Inovasi Nasional, 2025)
Affiliates now play a bigger role as consumers' main information source thanks to the growth of affiliate marketing in the digital commerce ecosystem. Customers' cognitive assessments are thought to be influenced by affiliate credibility, especially when evaluating risk and transaction value. The purpose of this study is to examine how affiliate trustworthiness affects perceived risk and perceived value, as well as how this affects the value of digital consumer transactions. 350 Indonesian digital customers who had encountered affiliate suggestions were surveyed as part of this study's quantitative methodology. Structural Equation Modeling (SEM) was used to assess the data. The findings demonstrated that perceived risk was significantly impacted negatively by affiliate credibility, whereas perceived value was significantly impacted positively. Additionally, transaction value was positively impacted by perceived value and negatively impacted by perceived risk. The results also demonstrated that the relationship between affiliate credibility and transaction value is mediated by perceived risk and perceived value. In addition to practical implications for businesses and platforms creating affiliate marketing strategies focused on lowering risk and raising customer transaction value, this study offers theoretical contributions to the development of source credibility-based digital marketing studies.